Ploughing with compact disc - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Compact discs can be used for more than just recording your favourite music. They can store all the information found in the largest agricultural encyclopedia. CD-ROM technology thus opens up a new avenue for communication techniques in development...